UPAYA PEMERINTAH INDONESIA DALAM MENINGKAT KAN EKSPOR JAGUNG INDONESIA KE MALAYSIA TAHUN 2012-2016 - Ridho Handoko; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Malaysia is Indonesia's largest corn market share for ASEAN countries, because the amount of world corn exports to Malaysia is relatively high compared to the number of world corn exports to other countries. Indonesia views that the corn market in Malaysia has potential prospects, where the value of corn exports has reached 42,265,616 per year in 1998. To meet the demand for the Malaysian corn market, Indonesia needs a strategy so that the growth of corn exports to Malaysia can grow and be fulfilled because the development of exports of Indonesian agricultural products (including corn) tends to fluctuate.The research method used in the study is a qualitative research method accompanied by interpretation of data obtained through references from publications, both from the news, journals, annual reports, and others. This research uses the perspective of liberalism and the level of analysis in the form of the Nation-State.This research will explain some strategic steps taken by the Indonesian government in order to try to meet the demand of the corn market from Malaysia, namely the development of the Export-Based Food Barn in the Border Area (LPBE-WP) which aims to place strategic regional locations in the border as a foundation for farming to export, internal improvements in the scope of farming, and increased cooperation in export-import in order to increase exports. Keywords : Indonesia, Malaysia, Import, Corn, Strategic Policy